Characterisation of Induced Rat Mammary Gland Tumor and the Antitumor Effect of Recombinant Human Erythropoietin and Tamoxifen - Abdul Karim, Sairah (2009)
Breast cancer is the most common cancer and the incidence and mortality rate had remained high. In Malaysia alone, breast cancers accounted for 31% of all new cancer cases and are among the most fatal cancers. Since breast cancers are complex diseases, there is no single marker that is both sensitive and specific for early detection of the disease. The present study was undertaken to characterize rat mammary gland tumors as a model for breast cancers and to determine parameters that could be used as early tumor markers. The study also undertook to determine the effect of recombinant human erythropoietin (rHuEPO) and Tamoxifen on the rat mammary gland tumor. In the first part of the study serum biochemical parameters, angiogenic factors and tumor markers, tumor histopathology and ultrastructure and expression of estrogen (ER) and erythropoietin receptors (EPOR) were determined. Twenty female Sprague-Dawley rats, aged six to seven weeks were divided into two groups of 10 rats per group. The rats were treated intragastrically, the first group with 20 mg 7,12-dimethylbenz(a)anthracene (DMBA) per rat to induce mammary tumor development and the second group with 1 mL 0.9% normal saline and served as the control. The animals were palpated weekly for tumor mass and sacrificed two weeks after tumor occurrence. Blood was withdrawn through cardiac puncture before tumor induction and weekly thereafter. Serum biochemical parameters analysed were alkaline phosphatase (ALP), aspartate aminotransferase (AST), alanine transferase (ALT), lactate dehydrogenase (LDH), creatinine kinase (CK), glucose, blood urea nitrogen (BUN) and creatinine by a chemistry analyser using standard diagnostic kits. Serum tumor markers,namely α-fetoprotein (AFP) and CA15-3 were analysed using automated immunoassay analyser, while the angiogenic factors, matrix metalloproteinase-2 (MMP-2) and vascular endothelial growth factor (VEGF) were determined by the ELISA technique. Tumor tissues excised from sacrificed animals were subjected to histopathological analysis and ER-α and EPOR determination through immunohistochemistry (IHC). Tumor ultrastructure was examined by transmission electron microscopy (TEM). The results showed higher ALT, ALP and AST concentrations in the DMBAtreated than the control group reflecting abnormal liver function. Pronounced increases in serum LDH were also observed in the DMBA-treated group. Angiogenic factor estimations showed that serum MMP-2 levels remained high throughout the study and seemed to have played a greater role than VEGF in early stage tumorigenesis. Serum tumor markers, AFP and CA 15.3 were not detected in either the treated or control rats. Histopathological analysis showed features typical of neoplastic cells which were enlarged nuclei, conspicuous nucleoli nuclear pleomorphism, high nuclear to cytoplasma ratio, hyperchromasia, and epithelial cell and stroma hyperplasia. These features are similar to that found in breast cancers. Immunohistochemical analysis showed that ER-α and EPOR were present in the DMBA-induced rat mammary tumor, which also resemble human breast cancers. Transmission electron microscopy analysis of the tumor demonstrated the co-existence of apoptosis, necrosis and aponecrosis which may be used in the determination of mammary gland tumor and breast cancer development in the early stages. In conclusion, the combination of serum liver-related enzymes, serum MMP-2 and histological changes, ER-α and EPOR expression, evidences of apoptosis, necrosis and aponecrosis may form the panel for screening and determination of early mammary gland tumors in high risk cancer patients. The second phase of the study involved the development of a xenograftinduced mammary gland tumor model in rats as a substitute for the conventional drug-induced method. The xenograft-induced mammary gland tumor seems to be reliable and can produce tumors within a short period. The xenograft model was then used to evaluate the effects of rHuEPO, Tamoxifen and Tamoxifen-rHuEPO combination on mammary gland tumor growth and angiogenesis. In this study, 24 rats were divided into four groups of six rats each. Each rat was treated orally: Group 1 with 60 IU rHuEPO; Group 2 with 20 mg Tamoxifen; Group 3 with a combination of 20 mg Tamoxifen and 60 IU rHuEPO; Group 4 with 1 mL 0.9% normal saline and served as the control. The results showed that rHuEPO did not promote mammary tumor growth and in fact may enhance the cytotoxicity of Tamoxifen through the stimulation of proapoptotic and antiproliferative effects. This study suggests that rHuEPO treatment in cancer patients may not only be beneficial for the alleviation of anemia due to the disease, but also augments the effect of certain chemotherapeutic drugs used in the treatment of cancer